Measurement of the production of charm jets tagged with D0 mesons in pp collisions at √s= 5.02 and 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2023)
The measurement of the production of charm jets, identified by the presence of a D0 meson in the jet constituents, is presented in proton–proton collisions at centre-ofmass energies of √s = 5.02 and 13 TeV with the ALICE detector at the CERN LHC. The D0 mesons were reconstructed from their hadronic decay D0 → K−π+ and the respective charge conjugate. Jets were reconstructed from D0-meson candidates and charged particles using the anti-kT algorithm, in the jet transverse momentum range 5 < pT,chjet < 50 GeV/c, pseudorapidity |ηjet| < 0.9 − R, and with the jet resolution parameters R = 0.2, 0.4, 0.6. The distribution of the jet momentum fraction carried by a D0 meson along the jet axis (zch ‖ ) was measured in the range 0.4 < zch ‖ < 1.0 in four ranges of the jet transverse momentum. Comparisons of results for different collision energies and jet resolution parameters are also presented. The measurements are compared to predictions from Monte Carlo event generators based on leading-order and next-to-leading-order perturbative quantum chromodynamics calculations. A generally good description of the main features of the data is obtained in spite of a few discrepancies at low pT,chjet. Measurements were also done for R = 0.3 at √s = 5.02 and are shown along with their comparisons to theoretical predictions in an appendix to this paper.
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S. Stiefelmaier, M. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1011 weitere]
Im Titel erscheint bei dem Ausdruck D0 die "0" hochgestellt
Gesehen am 17.10.2023